Developmental bisphenol A exposure impairs sperm function and reproduction in zebrafish. (February 2017) - Chen, Jiangfei; Saili, Katerine S.; Liu, Yueqin; Li, Lelin; Zhao, Yuxin; Jia, Yinhang; Bai, Chenglian; Tanguay, Robert L.; Dong, Qiaoxiang; Huang, Changjiang
Abstract: The developmental and reproductive toxicity of bisphenol A (BPA) has been demonstrated in a variety of model systems. Zebrafish ( Danio rerio ) were waterborne-exposed to BPA during three different developmental stages: embryonic period:6 h post fertilization (hpf) to 5 months post fertilization (mpf); larval period: 6 days post fertilization (dpf) to 5 mpf; and sexually mature period: 3 mpf to 5 mpf. Evaluations included F0 adult growth, reproduction parameters, and F1 offspring development. BPA exposure did not affect zebrafish growth in any of exposure groups. Testis weight was decreased only following the 6 hpf to 5 mpf 0.001 μM BPA exposure. The lowest effect level indicated by a reduction in sperm volume, density, motility, and velocity across a range of exposure durations was 0.001 μM, with all but sperm density significant for the longest exposure duration, which was also the only significant endpoint for the lowest exposure concentration in the 3–5 mpf exposure group. Nonmonotonic concentration-response curves were noted for all F0 reproductive endpoints for at least one of the two longest exposure durations. For the F1 offspring of fish exposed from 6 hpf to 5 mpf, malformations and mortality were increased following 0.001 μM BPA exposure, while egg production and fertilization were reduced in higher concentration treatment groups. Overall, BPA exposure during three different developmental periods impaired zebrafish reproductive development, with most significance changes found in the lowest concentration treatment groups. Genetic impacts on gamete development may underlie the secondary effects of reduced fertilization rate, embryonic mortality, and malformations. Highlights: The reproductive effects of environmental relevant level BPA in zebrafish were assessed. BPA impacted the sperm production and reproductive success for all developmental stages exposures. The overall effects of low dose (0.001 μM) were more severe than the high doses (0.1 and 0.01 μM).